Aplikasi Pemberitahuan Rapat pada STMIK Dumai Berbasis SMS Gateway - Putri Yunita; Masrizal Masrizal; Fitri Pratiwi (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Short Message Service (SMS) is a technology that provides service for sending and receiving messages between cell phones. Every individual, government, private or educational institution cannot be separated from using SMS as one of the information media. One of them is meeting notification information. But SMS technology can only carry limited data. SMS Gateway is a system that bridges mobile phones with the system that becomes a server with SMS as the information. In the SMS Gateway work system, the user's cellular phone sends an SMS containing the written format to access the information needed through the GSM network. The SMS will be received by the SMS Gateway cellular phone which will then be retrieved by the PC using the mfbus protocol via a data cable. Up to the PC, the text format will be processed by the SMS Gateway application program to produce information that will be sent to the SMS Gateway cellular phone using the mfbus protocol via a data cable. After that the information is sent by the SMS Gateway cellular phone to the user's cellular phone. With the SMS Gateway-based meeting notification application, it can provide detailed and concurrent notification of meeting information so that each meeting member can follow according to his schedule.